(3TQM GdebOeI GdCRgQjI aj Yde GdYQHjIs - (3GdLQLGhj GdCRgQj, GdhbGO, NGdO GdCRgQj, NGdO Hf YHO Gddg Hf CHj HcQ Hf eMeO, J (B905(3g` (B1499(3es
(3ChdgG (B:s
(3GdMeO ddg Ydi LejY GdCMhGd (B... (3GdcdGe YfO GddZhjjf YHGQI Yf Gdbhd heG cGf ecJajG HfaSg ceG PcQg aj GdbGehS, haj GUWdGM GdeJcdejf YHGQI Yf GdeYfi GdbGFe HGdfaSs
(3BNQgG (B:s
(3BNQgG(B: (3jhShS ef GdaYd hGdaGYd UdI GdPj (B.. (3aGYd jhShS GdeSJJQ ajg aj UOhQ LGQ heLQhQ eJYdb GjVG HjhShS hGdfGS eYWha Ydi GdLfI (B. (3haj gPG GdbOQ caGjI GdeHJOjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B2: 297s
(3cTa GdXfhf, L (B2: 1798s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdfMhs